FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS RASUAN TAHUN 2023 - Hafizhah, zahra nur; Wathan, Fika; Arif, Ahmad; Indriani, Putu Lusita Nati (Universitas Muhammadiyah Tangerang, 2023)
ARI (Acute Respiratory Infection) is an acute infection that attacks one or more parts of the respiratory tract from the nose to the alveoli, including the adnexa. ARI is one of the main causes of morbidity and mortality from infectious diseases in the world. Nearly four million people die from ARI every year. The groups most at risk are toddlers, children and the elderly, especially in countries with income in low and middle per capita. ISPA is caused by several factors, both individual and environmental, such as parental smoking habits, nutritional status of toddlers and basic immunization status of toddlers.The purpose of the study was to determine the factors that influence the incidence of acute respiratory infections (ARI) in toddlers in working area of UPTD of Rasuan Health Center in 2023. This study used an analytical survey method with a Cross Sectional” approach. The was conducted in June-July 2023 at the UPTD of Rasuan Health Center. The population in this study was the inhabitant who had toddlers in the working area of UPTD of Rasuan Health Center. The sample was taken using a systematic random technique (systematic random sampling) with total were 98 people.Based on the results of the chi-square statistical test between the variable of smoking habits of family member, toddler nutrition and basic immunization on the incidence of ARI, obtained the p value = 0.005 <0.05 (OR: 4.597), 0.000 <0.05 (OR: 0.007), 0 .02 <0.000 (OR : 0.039). So it can be concluded that there was a relationship between the smoking habits of family members, toddler nutrition and basic immunization on the incidence of acute respiratory infections for toddlers in the working area of UPTD of Rasuan Health Center in 2023. The results of the study are expected to provide information on the factors that influence the incidence of acute respiratory infections for toddlers.